2016
DOI: 10.1590/1809-98232016019.150156
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the functional capacity of elderly residents of communities with a rapid population aging rate

Abstract: Introduction: The elderly population has risen sharply in Brazil, increasing the need for a health policy focused on health promotion and disease prevention. Attention should also be focused on functional capacity because of the personal and family suffering caused by dependency, as well as the increased demand placed on public services. Objective: To check the health and functional capacity of elderly residents in a small town with a high population aging rate. Methods: A cross-sectional, analytical and non-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0
12

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 23 publications
2
18
0
12
Order By: Relevance
“…(3) This finding corroborates that found in a study carried out with elderly people living in the state of Rio Grande do Sul, Brazil, in which the fact that women live longer is not directly related to better health conditions or quality of life. (17) In regard to IADL and AADL according to sex, in our study, women were more dependent, with the exception of total dependence for IADL, which corroborated the literature, with women being more prevalent in all categories of AIDD. (3) When analyzing the age groups, the younger elderly people (60-70 years old) were the majority, which corroborated the data found in a study of 820 elderly people, in which 44.4% (n=250) were in the age group of 60 to 70 years old.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(3) This finding corroborates that found in a study carried out with elderly people living in the state of Rio Grande do Sul, Brazil, in which the fact that women live longer is not directly related to better health conditions or quality of life. (17) In regard to IADL and AADL according to sex, in our study, women were more dependent, with the exception of total dependence for IADL, which corroborated the literature, with women being more prevalent in all categories of AIDD. (3) When analyzing the age groups, the younger elderly people (60-70 years old) were the majority, which corroborated the data found in a study of 820 elderly people, in which 44.4% (n=250) were in the age group of 60 to 70 years old.…”
Section: Discussionsupporting
confidence: 90%
“…(18) The majority (44.4%, n=234) of the elderly people had 1-3 SRD, 31.7% (n=168) had 4-6, and 10.5% (n=55) had more than 6 diseases. (17) Decreased functional capacity may be due to a single disease or the sum of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…20 Os fatores que impulsionam o envelhecimento populacional são distintos de outras experiências, em parte, pela heterogeneidade econômica, social, cultural e ambiental. 21,22 Junto com o envelhecimento, nota-se o aumento sempenho cognitivo, como a redução da atenção e da velocidade do processamento de informação. 37 As mudanças psicológicas com o envelhecimento resultam da dificuldade de adaptações a novos papéis sociais, falta de motivação, baixa-estima, dificuldade de mudanças rápidas, perdas afetivas e orgânicas, somatização, hipocondria e depressão.…”
Section: O Processo De Envelhecimentounclassified
“…The need for emergency care of the elderly has gradually increased due to population aging and a changing epidemiological profile 1 . A study carried out in emergency departments in the USA found that the elderly, especially those over 75 years old, have a higher admission rate for emergencies than other age groups, a rate that is likely to increase as the population ages 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Increased life expectancy can result in the occurrence of problems arising from morphophysiological changes inherent to aging, leading to an increase in chronic diseases, morbidity and functional disability 1 . The elderly are therefore more likely to seek emergency care, and are usually admitted to the hospital twice as often as younger individuals 2 .…”
Section: Introductionmentioning
confidence: 99%